(untitled) (Biocenosis, 2025)
The UNED network initiative, promoted by the Rector’s Office of the Universidad Estatal a Distancia (UNED – State University for Distance Learning) in Costa Rica, aims to establish interactive spaces that strengthen student commitment and leadership across the various regions where UNED operates. The project focuses on creating collaborative nodes linked to the university’s regional centers, facilitating information exchange and skill development in research, entrepreneurship, environmental management, and soft skills. Through a participatory and multidisciplinary approach, Interconecta UNED (Uned network) seeks to empower students by providing them with tools to generate a positive impact in their communities, foster environmental sustainability, and contribute to the achievement of the Sustainable Development Goals (SDG), particularly those related to quality education, reduced inequalities and climate action.